Transformation of Calcium Carbonate Polymorph From Various Type of Shells by Carbonation Methods - Srie Muljani; Erwan Adi Saputra; Ketut Sumada (Reaktor, 2021)
The utilization of shells can reduce the accumulation of shell wastes and increase the value of shells to achieve ecological and economic incentives. This study examines the transformation of calcium carbonate polymorph from several types of shells to understand the causes of their characteristics in order to suitable for their use. The types of shells used in this experiment are selected based on consumable and their habitats such as snail shells, crab shells, eggshells, batik mussels shells, and golden conch shells. The prepared shells calcinate at 900 °C, the reaction with hydrochloric acid, and carbonation by flowing CO2 into a stirred reactor to produce precipitated CaCO3. The characteristics of polymorph CaCO3  in the sintering temperature of 30, 50, and 70 ℃ were identified by XRD, FTIR, and SEM morphological. The result is that the polymorphs formed from each shell are different in shape, size, and crystallinity. At the temperature of 70 ℃, the rhombohedral calcite was obtained from snail shells, the cubic calcite was obtained from batik mussel shell, while rhombohedral calcite multilayers obtained (100%) from golden conch shells. The aragonite was obtained from batik mussel shells at 30 and 70 ℃. The pure vaterite (100%) was obtained from snail shells and crab shells at 50 ℃. The characteristic of polymorph formed might be useful as information for more suitable applications, especially as nano-bio materials, optical, or filler